Systematic Review on Characterization of Tannase from Agricultural By-Products - Shah, Nurul Adlin Azaman; Mansor, Azlina; Manikam, Raseetha Vani Siva (Department of Agro-industrial Technology, University of Brawijaya, 2023)
AbstractTannin-rich compounds are widely produced as by-products of many agro-industrial processes. Tannase is an attractive hydrolase for the bioconversion of tannin-rich materials into value-added products by accelerating the hydrolysis of ester and depside linkages. It has opened new opportunities in several industrial sectors, such as food, drinks, and medicines. Primary sources of tannase are microorganisms, particularly bacteria. Tannases or tannin acyl hydrolases, are an important group of biotechnologically relevant enzymes in several industrial applications. Microbial tannases are mostly induced extracellular enzymes produced by submerged and solid-state fermentation. Tannins containing low-value agro-industrial wastes are being extensively used in industries. This review provides a more in-depth knowledge of the research related to the biochemical characteristics of the tannase enzyme activity (in terms of molecular weight, the effect of pH, the effect of temperature, the effect of metal ions, inhibitor, and chelator), extraction, and purification methods. Additionally, the potential use of agricultural waste as a substrate for tannase production has also been reviewed, including the utilization of pomegranate peel waste (PmPW), banana peel waste (BPW), or potato peel waste (PtPW).Keywords: agricultural waste, tannase, tannin AbstrakSenyawa kaya tanin diproduksi secara luas sebagai produk sampingan dari banyak proses agroindustri. Tannase adalah hidrolase yang menarik untuk biokonversi bahan kaya tanin menjadi produk bernilai tambah dengan mempercepat hidrolisis ikatan ester dan depside. Hal tersebut telah membuka peluang baru di beberapa sektor industri, seperti makanan, minuman, obat-obatan, dan sebagainya. Sumber utama tannase adalah mikroorganisme, terutama bakteri. Tannase atau tanin asil hidrolase, adalah kelompok penting dari enzim yang relevan secara bioteknologi yang digunakan dalam beberapa aplikasi industri. Tannase dari mikroba sebagian besar diinduksi enzim ekstraseluler dan diproduksi oleh fermentasi terendam dan fermentasi keadaan padat. Tanin yang terkandung dalam limbah agroindustri bernilai rendah banyak digunakan dalam industri. Ulasan ini memberikan pengetahuan yang lebih mendalam tentang penelitian terkait karakteristik biokimia aktivitas enzim tannase (dari segi berat molekul, pengaruh pH, pengaruh suhu, pengaruh ion logam, inhibitor, dan chelator), metode ekstraksi dan pemurnian. Selain itu juga telah dikaji potensi pemanfaatan limbah pertanian sebagai prekursor ekstrak tannase, antara lain pemanfaatan limbah kulit buah delima (PmPW), limbah kulit pisang (BPW), atau limbah kulit kentang (PtPW).Kata Kunci: limbah pertanian, tannase, tannin